ANALISIS KESESUAIAN IMPLEMENTASI BUDAYA ORGANISASI 7 KARAKTER PADA MAHASISWA UNIVERSITAS DHYANA PURA - Yeyen Komalasari (Forum Manajemen STIMI Handayani Denpasar, 2019)
Organizational Culture is a very important factor in improving organizational effectiveness. Organizational culture can be a major competitive advantage instrument, when organizational culture supports organizational strategies and can answer or overcome environmental challenges quickly and accurately. The Organizational culture "Undhira's Seven Characters" are: Self Confidence, Integrity, Pluralism, Intra-entrepreneurship, Servant Leadership, Professionalism, and Globaly. The study was conducted on 70 Undhira Management Study Program students who have completed 7 character learning. Based on the importance-performance analysis, the 14 indicators of 7 characters Undhira, only indicator of the Professional variable, namely Competent, who scores 103.23%, above 100%, this means that competent has been very strong effect to their behavior. But 13 other indicators have suitability levels below 100%, which means that the overall organizational culture of the 7 Characters Undhira have not been firmly rooted. Even so, it does not mean that the results obtained are bad, given the lowest suitability level of 80, 31% or above 50%, so the organizational culture of 7 characters can be well received, but the adaptation process must be carried out continuously. Based on the Cartesius Diagram, Quadrant A is an indicator whose handling needs to be prioritized, namely: Innovative capture opportunities, Ethics of superior work ethic, and Competitive collaboration interactions. Based on the Suitability Level Analysis, the indicator of competitive collaboration interaction needs to get the first priority in reform, because it has the lowest suitability level of 80.31 %. While the competent indicator gets the last priority because it has the highest suitability level of 103.23%.